THE FOUNDATIONS OF SELECTING CULTURAL TOURISM PRODUCT IN JORDAN - Alshawagfih, Kefah Fare Alnahar; Alananzeh, Omar Abedlla; Jawabreh, Omar A.A. (European Scientific Journal, ESJ, 2015)
This study comes to get acquainted with the adopted methods and principles of the procedure of choosing and conversion the culture milestone to tourism product by implementing Delphi method for testing and conclusion the requested information, which is summed up in asking set of questions, prepared in advance, on experts and consultants from the tourism sectors to stand on their opinions in the procedure and it’s dynamic of choosing the tourism product. The descriptive method was utilized to analyze the data and the information that has been collected through the interviews, and the available data in the books and the researches related to the research subject. The most significant results concluded by the study are that the factors for the sites of the culture tourism in Jordan contain three sets: The originality and the uniqueness of the sites; the merchandising and the marketing of the sites; and the issue of the political identity. As well the study showed the tourism centers, that are distinguished by the originality and the uniqueness have a big role in the tourism attraction. It was obvious that there is interference between maintaining the civilized inherited and the culture tourism; the culture tourism is based on three principles: maintaining the civilized inherited; converting it to tourism product; and investing it economically. It is clear that there is a possibility for the tourism territories to rise and develop under the globalism and the local societies could play a role in framing their own tourism territories through a national and international network system as the case in Petra, the Dead Sea and Aqaba.